Exploring English Education Students’ Experiences and Attitudes Toward Using Duolingo for Vocabulary Learning: A Qualitative Study at UNPARI - Anjas Moro (CV Grasta Glory, 2025)
Abstract: This study explores the experiences and attitudes of English Education students at Universitas PGRI Silampari (UNPARI) toward Duolingo, a mobile-assisted language learning (MALL) application, in developing English vocabulary. Using a qualitative descriptive design, six participants who had consistently used Duolingo for at least three months were selected through purposive sampling. Data were gathered through semi-structured interviews and analyzed thematically based on the framework proposed by Sundler et al. (2021). The analysis revealed four major themes: motivation through gamification, flexibility and accessibility, challenges of maintaining consistency, and the contextual relevance of vocabulary content. While Duolingo enhanced learner motivation and enabled flexible, autonomous learning, participants also reported limitations such as lack of sustained consistency and the mismatch between vocabulary content and their academic context. The findings suggest that Duolingo can serve as an effective supplementary tool for vocabulary development, particularly in regional university settings, when pedagogically integrated with formal instruction and localized learning support.